Le livre italien dans les collections de Montréal - Amélie Ferrigno (Diasporas: Circulations, Migrations, Histoire)
This article defines a new circuit of the Italian book through the analysis of the new “cultural network” (Sulpician priests and other lay possessors). Using an original survey of provenance marks in books printed in Italian language (15th-18th century) from collections in Montreal, as well as the analysis of the editions that made this trip across the Atlantic, this study measures the ways population integrated and how Italian humanism was locally assimilated by French settlers and natives of New France.